Absolute Reliability of Gait Parameters Acquired With Markerless Motion Capture in Living Domains - Riazati, Sherveen; McGuirk, Theresa E.; Perry, Elliott S.; Sihanath, Wandasun B.; Patten, Carolynn (Frontiers in Human Neuroscience, 2022)
PURPOSE: To examine between-day absolute reliability of gait parameters acquired with Theia3D markerless motion capture for use in biomechanical and clinical settings. METHODS: Twenty-one (7M, 14F) participants aged between 18-73 years were recruited in community locations to perform two walking tasks: self-selected and fastest-comfortable walking speed. Participants walked along a designated walkway on two separate days. Joint angle kinematics for the hip, knee, and ankle, for all planes of motion, and spatiotemporal parameters were extracted for determination of absolute reliability between-days. For kinematics, absolute reliability was examined using: full curve analysis (root mean square difference (RMSD)) and discrete point analysis at defined gait events using standard error of measurement (SEM). Absolute reliability of spatiotemporal parameters was also examined using SEM and SEM%. RESULTS: Markerless motion capture produced low measurement error for kinematic full curve analysis with RMSDs ranging between 0.96° – 3.71° across all joints and planes for both walking tasks. Similarly, discrete point analysis within the gait cycle produced SEM values ranging between 0.91° - 3.25° for both sagittal and frontal plane angles of the hip, knee, and ankle. The highest measurement errors were observed in the transverse plane, with SEM > 5° for ankle and knee range of motion. For the majority of spatiotemporal parameters, markerless motion capture produced low SEM values and SEM% below 10%. CONCLUSION: Markerless motion capture using Theia3D offers reliable gait analysis suitable for biomechanical and clinical use.